The Influence of Spirit at Work on Employee Productivity at PT Millenium Penata Futures Makassar - Jamaluddin Jamaluddin; Wiwi Indah Sari; Haedar Akib; Maya Kasmita; Andi Caezar To Tadampali (Pinisi Business Administration Review, 2019)
Each company strives to get employees involved in organizational activities by providing work performance in work  productivity as high as possible to realize the goal. The spirit at work is a mental attitude that is able to provide encouragement for someone to be able to work harder, faster, and better. This study aims to (i) know the description of the spirit at work of PT.Millennium Penata Futures. (ii) to find out the description of work productivity of PT.Millennium Penata Futures. (iii) to find out how much influence spirit at work  has on the productivity of employees of the Makassar branch of PT Millennium Penata Futures. Data collection techniques used are, observation, questionnaire and documentation. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis. The results of the study show that (i) spirit at work at PT.Millennium Penata Futures Manager is in the very high category (ii) employee productivity at PT. Millennium Makassar Futures Manager is included in the very high category (iii) spirit at work variables have a significant effect on employee productivity variables at PT. Millennium Penata Futures Makassar. Therefore, the higher spirit at work, the productivity of employees at PT. Makassar Millennium Penata Futures will also increase